The pan‐deacetylase inhibitor panobinostat suppresses the expression of oncogenic miRNAs in hepatocellular carcinoma cell lines. Issue 8 (23rd December 2013) - Henrici, Alexander; Montalbano, Roberta; Neureiter, Daniel; Krause, Michael; Stiewe, Thorsten; Slater, Emily Prentice; Quint, Karl; Ocker, Matthias; Di Fazio, Pietro
Abstract Deacetylase inhibitors (DACi) are a new class of drugs with a broad spectrum of mechanisms that favor their application in cancer therapy. Currently, the exact mechanisms and cellular effects of DACi have not been fully elucidated. In addition to their effects on histone acetylation, DACi can interfere with gene expression via miRNA pathways. Treatment with panobinostat (LBH589), a novel potent DACi, led to the highly aberrant modulation of several miRNAs in hepatocellular carcinoma (HCC) cell lines as shown by miRNA array analysis. Among them, hsa‐miR‐19a, hsa‐miR‐19b1 and the corresponding precursors were down‐regulated by panobinostat in TP53−/− Hep3B and TP53+/+ HepG2 cell lines; hsa‐miR30a‐5p mature form only was suppressed in both HCC cell lines, as confirmed by further RT‐qPCR analysis. In HCC cell lines, panobinostat caused the upregulation of the predicted miRNA targets APAF1 and Beclin1 protein levels. Transfection with oligonucleotides mimicking these miRNAs led to an increase in the viability rate of both cell lines as analyzed by impedance‐based real‐time cell analysis. In addition, transfecting miRNA mimicking oligonucleotides resulted in the decrease of APAF1, Beclin1 and PAK6 at the protein level, proving the regulating influence of the investigated miRNAs on gene final products. The overexpression of the above mentioned oncomiRs in Hep3B and HepG2 cell lines leads to cell proliferation and downregulation of cell death associated proteins. In our model, panobinostat exerts its anti‐cancer effect by suppressing these miRNAs and restoring the expression of their corresponding tumor suppressor targets. © 2013 Wiley Periodicals, Inc.